Pemanfaatan Software Artificial Intelligence Dalam Pengembangan Media Pembelajaran Mengenal Dan Membaca Bahasa Aksara Sasak Berbasis Mobile - Bahtiar, Hariman; Muallifatunnafiah, Hasna’; Nurhidayati, Nurhidayati (Fakultas Teknik Universitas Hamzanwadi, 2024)
The influence of global culture and modernization in the field of technology has had a major impact on the field of education, especially in learning and teaching methods. The technology which keeps developing rapidly and provides great opportunities to improve the quality and effectiveness of learning media is Artificial Intelligence technology. Based on the results of observations and interviews, 85% of the 19 third-grade students at SDN 3 Sekarteja found it difficult to recognize and read the Sasak script language in local content lessons. This research aims to overcome students' difficulties in recognizing and reading the Sasak script language at SDN 3 Sekarteja through the development of mobile-based interactive learning media that utilizes Artificial Intelligence tools to create, so that they can be used as a means of teaching and learning activities. This research was carried out using the methods of problem analysis, data collection, design stage, design stage, development stage, trial and implementation. The results showed a very good response which was evidenced by the results of testing interactive learning media showing a good response: the absence of errors and getting very good results regarding the implementation of interactive learning media at SDN 3 Sekarteja from the results of the questionnaire.